2018
DOI: 10.1093/mnras/sty1549
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of ArH+ dissociative recombination and electron-impact vibrational excitation

Abstract: Cross sections are presented for dissociative recombination and electron-impact vibrational excitation of the ArH + molecular ion at electron energies appropriate for the interstellar environment. The R-matrix method is employed to determine the molecular structure data, i.e. the position and width of the resonance states. The cross sections and the corresponding Maxwellian rate coefficients are computed using a method based on the Multichannel Quantum Defect Theory. The main result of the paper is the very lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…In Table 3, the equilibrium distances and corresponding well depths are collected for all NgH + under study, and compared with those reported previously. In particular, when the results obtained in the present work are compared with the available in the literature, the trends observed are depended on the 2016), (c) Gerivani et al (2015), (d) Stolyarov and Child (2005), (e) Alekseyev et al (2007), and (f) Abdoulanziz et al (2018).…”
Section: Ab Initio Electronic Structure Calculations and Pecsmentioning
confidence: 49%
See 3 more Smart Citations
“…In Table 3, the equilibrium distances and corresponding well depths are collected for all NgH + under study, and compared with those reported previously. In particular, when the results obtained in the present work are compared with the available in the literature, the trends observed are depended on the 2016), (c) Gerivani et al (2015), (d) Stolyarov and Child (2005), (e) Alekseyev et al (2007), and (f) Abdoulanziz et al (2018).…”
Section: Ab Initio Electronic Structure Calculations and Pecsmentioning
confidence: 49%
“…Previous theoretical studies on the ground state ArH + have also determined equilibrium energies and bondlengths from MP2, CCSD(T), and MRCI calculations (Hirst et al, 1992;Stolyarov and Child, 2005;Alekseyev et al, 2007;Coxon and Hajigeorgiou, 2016;Abdoulanziz et al, 2018), and in Table 3 some of them are listed. One can see that both CCSD(T)/CBS [56] and MRCI+Q values predict stronger Ar-H + interaction by 119 cm −1 and shorter bondlength by 0.0009 Å than the most recent results published so far (Abdoulanziz et al, 2018). (blue lines) and ArH + (green lines) as a function of R. Electric dipole moments µ are with respect to Ng atom as origin, while µ ′ with respect to the HeH + center of mass are also given for comparison reasons from (a) Hirst et al (1992), (b) Gerivani et al (2015), and (c) Juřek et al (1995).…”
Section: Ab Initio Electronic Structure Calculations and Pecsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) and (2) the produced diatom can be formed in an excited vibrational state (Denis-Alpizar et al 2017). The vibrational excitation of ArH + by electron-impact was investigated (Abdoulanziz et al 2018); however, the only theoretical study that reports the rate coefficients for the collision of ArH + with He (Bop et al 2017) was done using a two-dimensional potential energy surface (PES) at the explicitly correlated coupled cluster with single, double, and perturbative triple excitations (CCSD(T)-F12) level of theory where the diatomic molecule was considered as a rigid rotor. To our knowledge, a full three-dimensional PES for the ArH + +He complex does not exist; therefore, the vibrational relaxation for this collision has not been considered so far.…”
Section: Introductionmentioning
confidence: 99%